Effect of BaO on the structure and properties of bismuth-based low-melting glasses. (16th November 2020) - Yan, Dongyang; He, Feng; Cao, Xiuhua; Zhang, Bing; Ren, Haidong; Xie, Junlin; Xu, Jiajia; Liu, Xiaoqing
ABSTRACT: The effect of BaO on the structure and properties of bismuth-based low-melting sealing glasses (Bi2 O3 –B2 O3 –ZnO–SiO2 –Al2 O3 –BaO) were investigated by FTIR, 27 Al NMR and DSC. The results showed that when BaO content was less than or equal to 3 wt-%, BaO provided (O 2– ) free oxide ions, which made [AlO6 ] transform into [AlO4 ] and made [BO3 ] transform into [BO4 ]. The increase of [AlO4 ] and [BO4 ] enhanced the network structure and decreased the thermal expansion coefficient of glass-ceramic. But when BaO was more than 3 wt-%, a large amount of Ba 2+, considered as an external body of network, entered the gap of glass network and weakened the existing bridge oxygen vibration in the glass structure and increased the thermal expansion coefficient. Besides, the crystallisation ability of glasses would be promoted by increasing the heat treatment temperature or the BaO content. The formation of BaAl2 Si2 O8 crystal would improve the acidity resistance of the glass-ceramic to a certain extent.